The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3892/etm.2017.4582
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging of injuries to the visual centers of the brain in patients with type 2 diabetes and retinopathy

Abstract: Abstract. The present study aimed to investigate the ability of diffusion-weighted imaging (DWI) to identify injury to the visual centers of the brain in patients with type 2 diabetes with retinopathy. The study included 84 cases (63 patients with type 2 diabetic retinopathy and 21 healthy individuals) that were assessed using DWI. Diabetic patients were equally divided into three groups: Proliferative diabetic retinopathy (PDR), non-proliferative diabetic retinopathy (NPDR) and diabetic without retinopathy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(20 reference statements)
1
0
0
Order By: Relevance
“…38 A previous fMRI study revealed enhancement of FC between the left orbitofrontal gyrus and the temporal gyrus in T1DM patients, which suggested a compensatory or adaptive response to impaired functional areas in those patients. 8 Moreover, dysfunction in the OSFG has been observed in patients with DR. 11 , 39 In our study, enhanced FC between the bilateral V1 and OSFG indicated improved functional reorganization, which may relate to OSFG compensatory regulation or recruitment of visual resources from other regions.…”
Section: Discussionsupporting
confidence: 53%
“…38 A previous fMRI study revealed enhancement of FC between the left orbitofrontal gyrus and the temporal gyrus in T1DM patients, which suggested a compensatory or adaptive response to impaired functional areas in those patients. 8 Moreover, dysfunction in the OSFG has been observed in patients with DR. 11 , 39 In our study, enhanced FC between the bilateral V1 and OSFG indicated improved functional reorganization, which may relate to OSFG compensatory regulation or recruitment of visual resources from other regions.…”
Section: Discussionsupporting
confidence: 53%